2015
DOI: 10.3109/0284186x.2015.1011756
|View full text |Cite
|
Sign up to set email alerts
|

Proton beam versus photon beam dose to the heart and left anterior descending artery for left-sided breast cancer

Abstract: (2015) Proton beam versus photon beam dose to the heart and left anterior descending artery for left-sided breast cancer, Acta Oncologica, 54:7,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 22 publications
2
47
4
Order By: Relevance
“…The results of this comparison showed that proton treatments could improve target coverage and reduce normal tissue burden and the integral dose in both gated and free breathing patients. These results are comparable with and add to those from recent similar studies that only investigated whole breast treatments (Mast et al 2014, Lin et al 2015.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results of this comparison showed that proton treatments could improve target coverage and reduce normal tissue burden and the integral dose in both gated and free breathing patients. These results are comparable with and add to those from recent similar studies that only investigated whole breast treatments (Mast et al 2014, Lin et al 2015.…”
Section: Discussionsupporting
confidence: 81%
“…Investigating the potential of the technique for proton therapy was the subject of one study in this thesis (Paper IV) as few studies have investigated this aspect of proton therapy (Mast et al 2014, Lin et al 2015. The more general impact of the breathing motion on dose distributions from proton radiotherapy has been addressed in another study in this thesis (Paper V).…”
Section: Respiratory Gatingmentioning
confidence: 99%
“…Numerous dosimetric studies clearly support the advantage of PBT at improving target coverage while simultaneously decreasing dose to the heart, coronary vessels, lungs and contralateral normal tissue compared with photon advanced planning techniques. These advantages are evident whether the target is partial breast, whole breast/chest wall or breast/chest wall and regional lymph nodes (Table 1) [20,[37][38][39][40][41][42][43]. A recent paper assessed the potential absolute gains with PBT compared with photon therapy in patients with left-sided breast cancer requiring comprehensive nodal irradiation.…”
Section: Second Malignancymentioning
confidence: 99%
“…Dosimetric studies do support a potential benefit of PBT in reduction of heart, cardiac substructure and lung doses [41,64]. Patients with bilateral breast cancer, unfavorable anatomy and left-sided disease may be most likely to benefit from this approach (Figure 2).…”
Section: Clinical Applications For Pbt In Breast Cancermentioning
confidence: 99%
“…The sparing effects of proton radiotherapy on critical organs is particularly apparent in cases of left-sided BC where using IMPT, as compared with IMRT, allowed a 20-fold reduction of heart dose and for the left anterior descendens (LAD) artery region (a lower arm of the left coronary artery), which is a critical structure in the development of late cardiac complications [67,[75][76][77][78][79][80]. Such findings are indicative of a potential benefit in using proton radiotherapy for adjuvant radiotherapy of BC patients, especially when risk factors for cardiac complications are present [80].…”
Section: Breast Cancer (Bc)mentioning
confidence: 99%